The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1126/science.aaf4362
|View full text |Cite
|
Sign up to set email alerts
|

Layered and scrolled nanocomposites with aligned semi-infinite graphene inclusions at the platelet limit

Abstract: Two-dimensional (2D) materials can uniquely span the physical dimensions of a surrounding composite matrix in the limit of maximum reinforcement. However, the alignment and assembly of continuous 2D components at high volume fraction remain challenging. We use a stacking and folding method to generate aligned graphene/polycarbonate composites with as many as 320 parallel layers spanning 0.032 to 0.11 millimeters in thickness that significantly increases the effective elastic modulus and strength at exceptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 54 publications
3
106
0
1
Order By: Relevance
“…Here, we propose two possible routes: One might be to perpendicularly align and immobilize LDH nanosheets in a matrix to create ultrafast ion conduction pathways along nanosheet planes, similar to the reports on anisotropic hydrogels of cofacially aligned oxide nanosheets ( 57 , 58 ); the other might be to first assemble LDH nanosheets into large-area lamellar membranes (fig. S10), then scroll into Archimedean spiral fibers, similar to the preparation of layered and scrolled graphene-based nanocomposites ( 59 ), and finally cut along the direction perpendicular to the axis of the fiber to produce thin membranes with spiral ultrafast in-plane conduction pathways. Taking in consideration that various liquid-phase membrane formation techniques (for example, drop casting, vacuum filtration, and spin coating) are available, such technological innovations could enable the promises of LDH nanosheets as an inorganic anion exchange conductor for practical electrochemical devices.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we propose two possible routes: One might be to perpendicularly align and immobilize LDH nanosheets in a matrix to create ultrafast ion conduction pathways along nanosheet planes, similar to the reports on anisotropic hydrogels of cofacially aligned oxide nanosheets ( 57 , 58 ); the other might be to first assemble LDH nanosheets into large-area lamellar membranes (fig. S10), then scroll into Archimedean spiral fibers, similar to the preparation of layered and scrolled graphene-based nanocomposites ( 59 ), and finally cut along the direction perpendicular to the axis of the fiber to produce thin membranes with spiral ultrafast in-plane conduction pathways. Taking in consideration that various liquid-phase membrane formation techniques (for example, drop casting, vacuum filtration, and spin coating) are available, such technological innovations could enable the promises of LDH nanosheets as an inorganic anion exchange conductor for practical electrochemical devices.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the on‐chip planar interdigitated design, there is also a helical structure as shown in Figure c . Such a design may enhance the strength of the device …”
Section: Design Considerations and Performance Metrics For Microsupermentioning
confidence: 99%
“…CNTs and graphene have also been examined recently as nano-fillers in polymer matrices as they can provide moderate enhancement in modulus and strength at small loadings in combination with a significant increase of thermal and electrical conductivities of the host matrices [5][6] . Graphene in particular, offers certain advantages over CNTs as it can be handled much more easily and its high surface area makes it more effective as a potential filler for engineering polymers [7][8] . Moreover, recent studies have shown that single and few layer graphenes are very effective for reinforcing metals such as nickel and palladium due to the strong interfacial bonding that is developed between these two classes of materials 4,9 .…”
Section: Introductionmentioning
confidence: 99%